2016
DOI: 10.2166/wst.2016.229
|View full text |Cite
|
Sign up to set email alerts
|

Impact of aluminum chloride on process performance and microbial community structure of granular sludge in an upflow anaerobic sludge blanket reactor for natural rubber processing wastewater treatment

Abstract: In this study, granular sludge formation was carried out using an aluminum chloride supplement in an upflow anaerobic sludge blanket (UASB) reactor treating natural rubber processing wastewater. Results show that during the first 75 days after the start-up of the UASB reactor with an organic loading rate (OLR) of 2.65 kg-COD·m(-3)·day(-1), it performed stably with a removal of 90% of the total chemical oxygen demand (COD) and sludge still remained in small dispersed flocs. However, after aluminum chloride was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…The capacity of the ABR for TSS removal was greater than that of the UASB reactor. Nguyen et al have reported the influent and effluent TSS concentrations of 279 ± 128 mg/L and 72.4 ± 58.5 mg/L, respectively, using the UASB reactor for treating wastewater [6]. On the other hand, the influent and effluent TSS concentrations of 225 ± 125 mg/L and 43 ± 25 mg/L, respectively, were obtained for the ABR in this study.…”
Section: Reactor Performancesupporting
confidence: 43%
See 4 more Smart Citations
“…The capacity of the ABR for TSS removal was greater than that of the UASB reactor. Nguyen et al have reported the influent and effluent TSS concentrations of 279 ± 128 mg/L and 72.4 ± 58.5 mg/L, respectively, using the UASB reactor for treating wastewater [6]. On the other hand, the influent and effluent TSS concentrations of 225 ± 125 mg/L and 43 ± 25 mg/L, respectively, were obtained for the ABR in this study.…”
Section: Reactor Performancesupporting
confidence: 43%
“…The methane recovery ratio based on the total COD removal was 52.4 ± 33.6% during phase 2, while the removal efficiency for total COD in the form of methane improved to 81.3 ± 14.3% using the UASB reactor treating the same type of wastewater [6]. The maximum methane gas production of 29.8 NL/day was observed on the 177th day.…”
Section: Reactor Performancementioning
confidence: 95%
See 3 more Smart Citations